VOCATIONAL AND TECHNICAL EDUCATION: VERITABLE TOOL FOR EMPLOYMENT GENERATION AND POVERTY ALLEVIATION - Lawal, Nuhu Ishaq (Sokoto Educational Review, 2013)
Vocational and technical education was designed to serve as a functional education in which practical and qualitative education is enhanced. It is an integral part of total education which embodies such principles of practical doing, preparing an individual for self-reliance and integrated education to enhance economic and social progress. For any nation to develop, it requires appropriate education for its economic growth. Thus, this paper examines the implication of vocational and technical education in general; its involvement in the production of manpower with the requisite knowledge, skills and attitudes to harness resources which will yield the goods and services required by the general populace. The paper also examines the meaning, objectives, role, and problems of vocational and technical education with a view to improving the economic status and literacy of the average Nigerians as well as improving their living standard. Some recommendations such as provision of an enabling environment for preparation of students who intrinsically wish to follow careers in science and science related subjects as well as cultural imitation should be imbibed to speed up the level technological advancement were also proposed.